Sistem informasi pengelolaan data laundry berbasis web pada Al Laundry Cikarang - Yahya, Muhammad (Universitas Multi Data Palembang, 2024)
Al Laundry is a kilo washing service and washing services that are calculated per item including washing and drying and ironing services such as washing clothes, washing bad covers, washing blankets, washing dolls, washing bags, washing shoes, washing carpets, washing coats. The data management process in this laundry service activity is still manual. When customers come to hand over their goods, recording goods data and making notes still uses a manual system which is used as a reference for writing in the customer data ledger, there is the potential for paper to be lost or torn so that laundry customer data is lost. Transaction systems that are still manual and not yet optimal have found problems such as accumulation of archives and reports, slow flow of information, slow data search processes and difficult transaction report recaps. To overcome this problem, a laundry management information system is needed that can increase the effectiveness and efficiency of AL Laundry's business performance. The aim of this research is to produce a web-based software application using the PHP programming language and MySql database to design a Laundry Management System. The result of this design is to produce a Web-based application that can be an information medium to help laundry service businesses in managing laundry customer data.